The Effect of the Investments Made by the Firms Operating in BIST 100, whether they are Group or International, on Firm Performance - Yenilmez, Bahan (Fırat University, 2022)
In this study, the effects of investments made by 33 companies operating in the manufacturing sector in Borsa Istanbul during market slowdowns and expansions on firm performance were analyzed on a sectoral basis by separating them according to whether the firms are group or international. For this purpose, 33 companies in the BIST 100 index between the years 2000-2021 are separated according to whether they are group or international; their investments have been determined and It is compared whether there is a significant relationship between the investments made by these companies, whether they are group or international companies, and the performance of the company and the direction and degree of this effect are compared and analyzed. In the study, firm performance was measured by the return on assets (ROA), the return on assets of cash flows (return on cash flows), Tobin's q, closing prices, rate of increase in assets, total shareholder return and earnings per share. According to the results of the study, the investments made by international companies operating in the Cement, Glaass and Tire Industries increase the performance of the company during periods of slowdown in the economy. But in the same period, the investments decrease the performance of the company in the Energy and Electronic sector. In the periods when the markets enter the expansion trend, based on all these results, the investments made by the international companies operating in the Cement and Glass Industry will increase the firm's performance. But in the same period, the investments decrease the performance of the company in the Energy and Tire sector. However again in the same period, there is no significant relationship between the investments and firm performance in the Electronic sector. For group companies, based on all these results, the investments made by the group companies operating in the Cement, Energy and Tire industries during periods of slowdown increase the company performance. However again in the same period, there is no significant relationship between the investments made by the international companies operating and firm performance in the Electronic and Glass sector. In the periods when the markets enter the expansion trend, the investments made by the group companies operating in the Cement, and Tire industry increase the company performance. But in the Energy sector the investments decrease the performance. Also, there is no significant relationship between the investments and firm performance in the Electronic and Glass sector.

Bu çalışma, Borsa İstanbul’da imalat sektöründe faaliyet gösteren 33 adet firmanın piyasa yavaşlamalarında ve genişlemelerinde yapmış oldukları yatırımların firma performansı üzerindeki etkileri sektörel bazda firmaların grup ve uluslararası olup olmamalarına göre ayrıştırılarak incelenmiştir. Bu amaçla 2000-2021 yılları arasında BIST 100 endeksinde yer alan 33 adet firma grup veya uluslararası olup olmadığına göre ayrıştırılarak; yapmış oldukları yatırımlar saptanmış ve bu firmaların grup veya uluslararası firma olup olmalarının yaptıkları yatırımların firma performansı ile aralarında anlamlı bir ilişki olup olmadığı araştırılarak ve bu etkinin yönü ve derecesi karşılaştırılarak analiz edilmiştir. Çalışmada firma performansı, varlık getiri oranı (ROA), nakit akışlarının varlık getiri oranı (nakit akışı getirisi), Tobin’s q, borsa kapanış fiyatları, varlıklardaki artış oranı, toplam performans, toplam hissedar getirisi ve hisse başına kazanç ile ölçülmüştür. Yapılan çalışmanın sonuçlarına göre ekonominin yavaşladığı dönemlerde Çimento, Cam ve Lastik sektöründe faaliyet gösteren uluslararası firmaların yapmış oldukları yatırımlar firma performansını arttırmakta; Enerji ve Elektronik Sektöründeki firmaların yapmış oldukları yatırımlar firma performansını azaltmaktadır. Piyasaların genişleme trendinin içine girdikleri dönemlerde ise tüm bu sonuçlar baz alındığında, Çimento ve Cam sanayisinde faaliyet gösteren uluslararası firmaların yapmış oldukları yatırımlar firma performansını arttırmakta; Enerji ve Lastik sektörlerindeki firmaların yapmış oldukları yatırımlar firma performansını azaltmakta; Elektronik sektöründe faaliyet gösteren firmaların yaptıkları yatırımlar ile firma performansı arasında herhangi anlamlı bir ilişki bulunmamaktadır. Grup firmaları için tüm bu sonuçlar baz alındığında, ekonominin yavaşladığı dönemlerde Çimento, Enerji ve Lastik sanayisinde faaliyet gösteren grup firmaların yapmış oldukları yatırımlar firma performansını arttırmakta; Elektronik ve Cam sektörlerinde faaliyet gösteren firmaların yaptıkları yatırımlar ile firma performansı arasında herhangi anlamlı bir ilişki bulunmamaktadır. Piyasaların genişleme trendinin içine girdikleri dönemlerde ise Çimento ve Lastik sanayisinde faaliyet gösteren grup firmaların yapmış oldukları yatırımlar firma performansını arttırmakta; Enerji sektöründeki firmaların yatırımları firma performansını azaltmakta; Elektronik ve Cam sektörlerinde faaliyet gösteren firmaların yaptıkları yatırımlar ile firma performansı arazasında herhangi anlamlı bir ilişki bulunmamaktadır.
BIST 100’DE FAALİYET GÖSTEREN FİRMALARIN ULUSLARARASI VEYA GRUP OLUP OLMAMASINA GÖRE YAPTIKLARI YATIRIMLARIN FİRMA PERFORMANSI ÜZERİNDEKİ ETKİSİ